2007
DOI: 10.1093/aob/mcm288
|View full text |Cite
|
Sign up to set email alerts
|

Eelgrass Meadows in the California Channel Islands and Adjacent Coast Reveal a Mosaic of Two Species, Evidence for Introgression and Variable Clonality

Abstract: The pristine environmental conditions of offshore islands do not guarantee maximum genetic diversity. Future restoration and transplantation efforts of seagrasses must recognize cryptic species and consider the degree of both genetic and genotypic variation in candidate donor populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Our study adds additional data from closer to the geographic margin of the species, and further supports the observation of a trend of increased diversity with decreased latitude. Compared to the western Atlantic and eastern Pacific populations studied (Reusch et al 2000, Olsen et al 2004, Talbot et al 2004, Coyer et al 2007, Ort et al 2010, WyllieEcheverria et al 2010, the Chesapeake and Virginia coastal bay populations described here are more diverse. The only meadows found to have higher values of heterozygosity and numbers of alleles per locus were in Mikawa Bay, Japan (Yoshida et al 2009; Table 4, present study).…”
Section: Discussionmentioning
confidence: 55%
“…Our study adds additional data from closer to the geographic margin of the species, and further supports the observation of a trend of increased diversity with decreased latitude. Compared to the western Atlantic and eastern Pacific populations studied (Reusch et al 2000, Olsen et al 2004, Talbot et al 2004, Coyer et al 2007, Ort et al 2010, WyllieEcheverria et al 2010, the Chesapeake and Virginia coastal bay populations described here are more diverse. The only meadows found to have higher values of heterozygosity and numbers of alleles per locus were in Mikawa Bay, Japan (Yoshida et al 2009; Table 4, present study).…”
Section: Discussionmentioning
confidence: 55%
“…Meadows may be heterogeneous as a consequence of temporal admixture events of repeated recruitment through time (originally proposed by Petit et al 2003for oaks, Becheler et al 2010; limited dispersal of pollen and seeds, leading to patchiness (Hämmerli & Reusch 2003); and local habitat selection (Oetjen & Reusch 2007, Oetjen et al 2010, Winters et al 2011. Alternatively, they can be homogeneous as a consequence of dominance by a few large genets/clones (Reusch et al 1999, Coyer et al 2008) and limited recruitment (Duarte et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have supported relationships to the northern islands for a variety of taxa, including tortricid Lepidoptera (Landry et al 1999, Rubinoff andPowell 2004), deer mice Wills 1987, 1989), eelgrass (Coyer et al 2008), dune spiders (Ramirez and Beckwitt 1995), and dune beetles . Some Hy.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have suggested relationships between Santa Catalina and San Clemente islands, in particular eelgrass (Coyer et al 2008), side-blotched lizards (Mahoney et al 2003), Loggerhead Shrikes (Eggert et al 2004), and one species of dune beetle . The species examined here show little indication of southern island relationships.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation